Penggunaan Bahasa Jurnalistik dalam Penulisan Berita Metrojambi.Com - Febrina Ita Fitri Anti; Agus Salim; Jamaluddin Arsyad (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2020)
The application of journalistic language in the news media is a must. Good news is news that uses simple language and is easily accepted by readers' logic. However, not all parties involved in news production understand the importance of using journalistic language in news writing in the mass media, including journalists and editors at MetroJambi.com where the research was conducted. As the best online media in 2016 in Jambi, MetroJambi.com still contains language errors in its news. The purposes of this study are (1) to find out the profile and background of the birth of the metrojambi.com news portal (2) to examine the use of journalistic language on the metrojambi.com news portal (3) to examine the efforts made by Metrojambi.com in overcoming the errors in the use of journalistic language in the media. the. The research method that the author uses is qualitative with a news content study approach. The data collection technique was carried out in two ways, first by interviewing the editor of Metrojambi.com, the General Manager of metrojambi.com, and the Head of the Jambi Language Office, as well as three Extension Officers of the Jambi Language Office. Second, collecting news from 01 September 2019 to 09 September 2019 which is then analyzed and described in this study. As a result, the researchers found that: first, Metrojambi.com came from the Metro Jambi print media, secondly, there were 7 errors in the use of journalistic language in news writing on Metrojambi.com from September 01, 2019 to September 09, 2019. This seems to make Metrojambi.com no longer entered in the best media category in Jambi Province in 2019, the three editors and general manager of Metrojambi.com provided training to journalists on reporting and writing, always involving journalists in training and counseling activities organized by the AJI organization, Jambi Language Office and all related to the activities of journalists, as well as the editors of Metrojambi.com also conduct more thorough research than before, in order to minimize writing errors in the news. The study recommends Metrojambi.com to pay attention to the use of journalistic language in published news, as well as to provide journalists with an understanding of the procedures for writing news that are in accordance with good and correct journalistic language.